Assessment of Left Ventricular Diastolic Function in Egyptian Patients With Behçet’s Disease - Heba FAROUK,; Hania Salah ZAYED,; Basma SAKR,; Geilan MAHMOUD, (Archives of Rheumatology, 2016)
Objectives: This study aims to evaluate left ventricular diastolic function in Egyptian patients with Behçet’s disease using variable echocardiographic parameters by combining both transmitral and tissue Doppler velocities to overcome the occasional false interpretation of preload dependent transmitral parameters and to detect the correlation between various left ventricular diastolic parameters and different disease manifestations. Patients and methods: Forty patients (35 males, 5 females; mean age 31±8 years; range 19 to 52 years) with Behçet’s disease and 32 age- and sex- matched healthy controls (26 males, 6 females; mean age 28±6 years; range 19 to 60 years) were enrolled. Left ventricular diastolic function was assessed using an algorithm that combined transmitral and tissue Doppler derived parameters. Results: Mean disease duration of the patients was 7.4±6 years. Left and right ventricular systolic function was normal in both groups. The transmitral E/A was <1 in six patients (15%). There was no difference between patients and controls regarding the other left ventricular diastolic parameters. Compared to patients with an E/A ratio >1, patients with E/A <1 were significantly older and had a longer disease duration (p=0.001 and p<0.001, respectively). All the other echocardiographic parameters in both groups were comparable. Conclusion: Egyptian patients with Behçet’s disease have normal left ventricular diastolic function regardless of disease duration and activity.